2012
DOI: 10.1007/s10611-012-9376-z
|View full text |Cite
|
Sign up to set email alerts
|

The bluntness of incarceration: crime and punishment in Tallahassee neighborhoods, 1995 to 2002

Abstract: The relationship between crime and incarceration is vexed. Some scholars suggest that incarceration deters crime. Others suggest that incarceration can increase crime in certain situations by undermining the social fabric and making the environment more criminogenic. Most of the empirical work on the question is undertaken at an aggregate level (county, state, or national data). Yet, criminologists have long argued that the complex intertwining of crime and punishment is best understood at the neighborhood lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…A series of studies conducted on data collected by Clear and colleagues on 80 neighborhoods in Tallahassee (Clear 2007, Clear et al 2003, Dhondt 2012) found that higher rates of prison admission and release in neighborhoods were associated with higher rates of crime, as predicted by coercive mobility theory. Another finding from these studies is that the association between rates of prison admission and crime was nonlinear: the relationship was not significant when the admissions rate was low, but once it reached a moderate level, additional increases to the admissions rate were significantly associated with higher crime rates, consistent with coercive mobility theory.…”
Section: Effects Of Incarceration and Reentry On Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies conducted on data collected by Clear and colleagues on 80 neighborhoods in Tallahassee (Clear 2007, Clear et al 2003, Dhondt 2012) found that higher rates of prison admission and release in neighborhoods were associated with higher rates of crime, as predicted by coercive mobility theory. Another finding from these studies is that the association between rates of prison admission and crime was nonlinear: the relationship was not significant when the admissions rate was low, but once it reached a moderate level, additional increases to the admissions rate were significantly associated with higher crime rates, consistent with coercive mobility theory.…”
Section: Effects Of Incarceration and Reentry On Communitiesmentioning
confidence: 99%
“… 11 In the Dhondt (2012) study, the relationship between incarceration and crime was nonlinear only when the former was measured with a scale combining rates of prison admissions and releases. …”
mentioning
confidence: 99%
“…A consequence of mass incarceration is large numbers of prisoners released back into the community. Although a handful of studies have examined the potential effects of parolees on neighborhood crime (Dhondt, 2012; Hipp & Yates, 2009) or parolee recidivism (Chamberlain & Wallace, 2016), these studies have failed to account for how parolees might affect changes in the broader neighborhood structure. The results from this study indicate that parolees can have a significant impact on neighborhoods beyond just increasing crime.…”
Section: Discussionmentioning
confidence: 99%
“…First, the relationship between parolees and neighborhood crime is cyclical. Prior research has found that parolees affect neighborhood crime, generally finding a positive association (Dhondt, 2012; Hipp & Yates, 2009; Kovandzic, Marvell, Vieraitis., & Moody, 2004; Raphael & Stoll, 2004). For example, some studies have found that parolees might increase crime directly by taking advantage of criminal opportunities in the neighborhood (Dhondt, 2012; Hipp & Yates, 2009), or increasing the pool of crime targets (Rosenfeld, Wallman, & Fornango, 2005).…”
Section: Parolees’ Indirect and Reciprocal Effects On Neighborhood Stmentioning
confidence: 99%
See 1 more Smart Citation